Using Expectancy Value Theory to understand motivation, persistence, and achievement in university‐level foreign language learning - Nagle, Charles (Foreign language annals, 2021)
Most students take language courses at university, but only a fraction go beyond the introductory and intermediate levels despite the fact that continued study is likely necessary to achieve full communicative competence in the target language. By shedding light on the motivational pathways that predict language learning effort, persistence, and achievement, motivation research can provide actionable data that can guide strategies to help students generate and maintain motivation, leading to better learning outcomes and a stronger and healthier language program for educators and administrators. This survey‐based study applied Expectancy Value Theory to understand links between motivation, persistence, and achievement in a fourth‐semester Spanish course, a critical transition point in the language curriculum. Expectancy Value Theory subcomponents showed differential relationships to willingness to communicate, enrollment choices, and final course grade. Based on this data, suggestions are offered for supporting university students' language learning interest and achievement. The Challenge Why do so many students stop taking foreign language courses after their first or second year? What can language educators do to support students' language learning persistence and achievement? Motivation research can shed light on these questions by providing insight into the dimensions of motivation that predict achievement‐related behaviors.